In His Milieu Essays on Netherlandish Art in Memory of John Michael Montias - Mochizuki, Mia M.; Golahny, A.; Vergara, L. (Amsterdam University Press, 2007)
Collected in memory of the Vermeer scholar and Yale economist J. Michael Montias, these essays take into account the latest trends in the field and provide new data on a wide range of topics in Netherlandish art. Themes include the reception of paintings and architecture; art collecting as interpreted through inventories and other documents that reveal modes of display; relationships between patrons and painters; recently found or attributed works of art; artists as teachers; and the art market. Taken together, these focused studies offer fresh perspectives on the historical appreciation and evaluation of art. Drawing upon J.M. Montias' contribution to art history, these 32 essays present new analyses, attributions, and documents on Netherlandish art and material culture - including the work of Vermeer, Rubens, Rembrandt, van Eyck and others - by internationally known scholars of art history and the economics of art